Shipboard ADCP current measurements (75 kHz) during RV METEOR cruise M189/2 - Steffen Ziegler; Robert Kopte; Stefan Kinne (PANGAEA, 2023)
Current velocities of the upper water column along the cruise track of R/V Meteor III cruise MET189_2 were collected by a vessel-mounted 75 kHz RDI Ocean Surveyor ADCP. The ADCP transducer was located at 5.0 m below the water line. The instrument was operated in narrowband mode (WM10) with a bin size of 8.00 m, a blanking distance of 4.00 m, and a total of 100 bins, covering the depth range between 17.0 m and 809.0 m. Heading, pitch and roll data from the ship extquotesingles motion reference unit and the navigation data from the Global Positioning systems were used by the data acquisition software VmDAS internally to convert ADCP velocities into earth coordinates. The ship extquotesingles velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Accuracy of the ADCP velocities mainly depends on the quality of the position fixes and the ship extquotesingles heading data. Further errors stem from a misalignment of the transducer with the ship extquotesingles centerline. Data post-processing included water track calibration of the misalignment angle (0.0202° +/- 0.5889°) and scale factor (1.0037 +/- 0.0135) of the Ocean Surveyor signal. The velocity data were averaged in time using an average interval of 60 s. Velocity quality flagging is based on following threshold criteria: abs(UC) or abs(VC) > 1.5 m/s, rms(UC_z) or rms(VC_z) > 0.3.